Mitochondrial adenine nucleotide translocase is modified oxidatively during aging - Yan, Liang-Jun (The National Academy of Sciences, 1998)
The purpose of this study was to test the hypothesis that elevation in protein oxidative damage during the aging process is a targeted rather than a stochastic phenomenon. Oxidative damage to proteins in mitochondrial membranes in the flight muscles of the housefly, manifested as carbonyl modifications, was detected immunochemically with anti-dinitrophenyl antibodies. Adenine nucleotide translocase (ANT) was found to be the only protein in the mitochondrial membranes exhibiting a detectable age-associated increase in carbonyls. The age-related elevation in ANT carbonyl content was correlated with a corresponding loss in its functional activity. Senescent flies that had lost the ability to fly exhibited a relatively higher degree of ANT oxidation and a greater loss of functional activity than their cohorts of the same age that were still able to fly. Exposure of flies to 100% oxygen resulted in an increase in the level of ANT carbonyl content and a loss in its activity. In vitro treatment of mitochondria with a system that generated hydroxyl free radicals caused an increase in ANT carbonyl level and a decrease in ANT exchange activity. ANT was also the only mitochondrial membrane protein exhibiting adducts of the lipid peroxidation product 4-hydroxynonenal. Results of this study indicate that proteins in mitochondrial membranes are modified selectively during aging.